Aneurysmal femoral neck cyst: Report of a paediatric case and review of literature - Oumar Ndour; Rodia Boseba; Jacque Barre Damipi; Juvenal Nibagora; Aimee Lakh Faye Fall; Gabriel Ngom; Mamadou Ndoye (Wolters Kluwer Medknow Publications, 2016)
The aneurysmal bone cyst (ABC) is a benign tumour of children and young adults. It represents approximately 1-2% of all bone tumours. The ABC may develop on all skeletal bones, but the proximal end of the femur is the most common location. The authors report a ABC femoral neck in a child of 13 years. This location is pretty special. Indeed, the fragility of the femoral neck due partly to the pathology itself and secondarily curettage requires a judicious attitude surgical (excisional curettage + bone graft + screw) to prevent the risk of high local recurrence and pathological fracture.